Integrasi Model Hibrida TOPSIS-BORDA untuk Penentuan Prioritas Strategi Digitalisasi Pesantren yang Berkelanjutan - Shofi Putri Lathifah; Adzhal Arwani Mahfud; Wenty Dwi Yuniarti; Khotibul Umam (Forum Kerjasama Pendidikan Tinggi, 2026)
Digital transformation in Islamic boarding schools (pesantren) holds a specific urgency as these institutions face the challenge of integrating administrative governance modernization with the preservation of salaf traditions, a dilemma rarely found in general formal education. Resource limitations and preference differences among leaders and administrators often trigger strategic deadlocks. This study aims to determine sustainable digitalization strategies at Pondok Pesantren YPMI Al-Firdaus Semarang by integrating the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and Borda Count. The TOPSIS model is utilized to objectively evaluate the technical feasibility of seven criteria, while BORDA facilitates quantitative deliberation to accommodate the preferences of five decision-makers. The analysis results indicate that alternative A1 (Digitalization of Administrative Management) becomes the main priority with a relative closeness value of 0.738 and a BORDA consensus score of 8.7664. This figure significantly outperforms other alternatives, proving that the improvement of basic administration is the most urgent and mutually agreed-upon foundation before the pesantren advances to more complex digitalization. Although this study is on a local scale, the integration of these methods proves effective in mapping social and technical compromises, and can be adapted by other pesantren with similar characteristics.